Computed Radiography of Chest Radiographic Imaging: A Phantom Study of Optimal Imaging Parameters and Radiation Dose - Sun, Zhonghua; Siddiqu, S.; Ng, K.; Ramli, K.; Davidson, R. (Philippine Organization of Medical Physicists, 2007)
Introduction: In chest radiographic imaging, computed radiography (CR) has been replacing the conventional film-screen imaging technology. Selection of the appropriate radiation quality is an important aspect of optimisation for chest imaging as it affects both image quality and patient dose. We aimed to investigate the optimal imaging parameters for chest radiographic imaging using CR system, with regards to the relationship between tube potential and radiation dose.Methods: The study was performed on a chest phantom made from sheets of plastic tubing, copper and aluminium, which were shaped to resemble frontal radiographic projections of human thoracic structures. Regional test objects were incorporated into the chest phantom for image quality assessment in the lungs, heart and retrodiaphragmatic areas. Chest phantom images were taken using CR on an Agfa system. Imaging parameters were selected with mAs ranging from 0.5, 1.0, 2.0, 4.0 and 8.0, and tube potential ranging from 100, 110 and 120 kV. Entrance skin dose (mGy) was measured using a solid state detector. Quantitative measurements of image quality were performed at 7 regions of interest to determine the relationship between image noise and imaging parameters.Results: The radiation dose increased significantly when the mAs was increased (p<0.05). However, no significant difference of radiation dose was found among the varying kV values (p>0.05). The image noise measured in different regions of interest increased significantly (p<0.001) when the kV was increased, with 120 kV generating the lowest noise value. Subjective assessment of image quality showed that chest radiographic images acquired with 2 mAs and 4 mAs were acceptable for diagnostic purpose.Discussion: Optimisation of CR imaging means that image quality must satisfy the diagnostic requirements for making a correct diagnosis at the lowest possible radiation dose. The findings in this study suggested that image quality improved with increased kV without any significant increase in radiation dose.Conclusion: Our results showed that CR chest radiography produced optimum image quality following the protocol of 120 kV and 2 mAs. The chest image quality in CR imaging can be improved by increasing the tube potential while maintaining relatively low dose.